Enhancing Animal Physiology Practicum: Exploring Students' Perceptions and Influencing Factors - Sri Pratiwi Yanti Arsyam; Martin N Kariuki (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: The purpose of this study was to determine the perception of Biology Education students towards the implementation of Animal Physiology practicum in the Biology Education Laboratory and to determine the factors that influence student perceptions towards the implementation of the practicum. This study aims to provide insight into improving the quality of practicum learning in higher education. Methodology: This type of research is descriptive with qualitative and quantitative approaches. The subjects of the study were fourth semester Biology Education students of UIN Alauddin Makassar. Data collection techniques used a Likert scale questionnaire 1–5 and documentation. Data analysis techniques include descriptive qualitative analysis for narrative data and quantitative analysis for questionnaire data in a descriptive-qualitative manner. Main Findings: The main findings of this study show that students perceive teaching assistants as supportive in guiding practicum groups, though there are issues with punctuality. Facilities and infrastructure, including laboratory cleanliness and equipment, are generally adequate but require improvement. Students report better understanding of animal physiology post-practicum, and active participation during the exercises. However, some students were not diligent with preliminary tasks, and there were discrepancies in the provision of assignments and material explanations. Novelty/Originality of this study: This study offers a unique perspective by integrating the roles of teaching assistants and laboratory assistants in shaping student perceptions of animal physiology practicums. It highlights the importance of punctuality, material explanations, and active involvement, providing practical insights for improving laboratory-based learning.